Estudo da temperatura de pastas com substituição parcial da silica ativa ao cimento utilizando o método semi-adiabático - (:unkn) unknown (Universidade Federal do Amazonas, 2017)
The increasing requests for shorter execution times in concrete using concrete results in a consequent demand for thermal control. This work aims to evaluate the use of silica in the reduction of temperature in cement reactions through tests on cement pastes using device and semi-adiabatic method developed in this research. For that, an equipment and method of use was developed. This work presents a method, including the design of the semi-adiabatic reaction measuring device, with the application of suitable materials to obtain the results, as well as an adequate experimental planning, allowing the evaluation of the active silica as a thermal control proposal. The results showed the different temperature indications, according to the respective dosages of active silica. The dosages of cement were substituted by silica in the proportions of 0, 7, 14 and 20% both with respect to w / c relation of 0.5. The silica was presented increasing or decreasing the temperatures of the reactions according to dosage, aspect, therefore, determinant to the process of application of the same for such purpose according to the data observed.
Keywords: Método Semi Adiabático Alternativo; Planejamento experimental; Reação exotérmica do concreto; Projeto térmico do concreto massa; Sílica ativa; Controle Térmico; ENGENHARIAS: ENGENHARIA CIVIL